2011
DOI: 10.1038/emboj.2011.22
|View full text |Cite
|
Sign up to set email alerts
|

Food sensitizesC. elegansavoidance behaviours through acute dopamine signalling

Abstract: Many behavioural states are modulated by food availability and nutritional status. Here, we report that in Caenorhabditis elegans, the presence of an external food source enhances avoidance responses to soluble repellents sensed by the polymodal ASH neurons. This enhancement requires dopamine signalling and is mimicked by exogenous dopamine. Food modulation is dependent on the mechanosensory cilia of the dopaminergic neurons, indicating that dopamine is released in response to sensation of bacteria. Activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(166 citation statements)
references
References 56 publications
8
156
1
1
Order By: Relevance
“…Our optogenetic assays used a chromosomally integrated transgene, ljIs102 (Ezcurra et al 2011), to express the bluelight-activated cation channel, channelrhodopsin-2 (ChR2) fused to the yellow fluorescent protein (YFP). A fragment of the promoter for the tph-1 gene (Sze et al 2000) was used to drive expression of ChR2::YFP specifically in serotonergic NSM and ADF neurons ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our optogenetic assays used a chromosomally integrated transgene, ljIs102 (Ezcurra et al 2011), to express the bluelight-activated cation channel, channelrhodopsin-2 (ChR2) fused to the yellow fluorescent protein (YFP). A fragment of the promoter for the tph-1 gene (Sze et al 2000) was used to drive expression of ChR2::YFP specifically in serotonergic NSM and ADF neurons ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Do MOD-1 and SER-4 have a normal physiological role in the control of locomotion by endogenously released serotonin? We initially addressed this question by optogenetically stimulating neurotransmitter release from the serotonergic neurons of C. elegans and measuring whether MOD-1 and SER-4 affect the resulting locomotion response.Our optogenetic assays used a chromosomally integrated transgene, ljIs102 (Ezcurra et al 2011), to express the bluelight-activated cation channel, channelrhodopsin-2 (ChR2) fused to the yellow fluorescent protein (YFP). A fragment of the promoter for the tph-1 gene (Sze et al 2000) was used to drive expression of ChR2::YFP specifically in serotonergic NSM and ADF neurons ( Figure 4A).…”
mentioning
confidence: 99%
“…An alternative approach uses FLP or Cre recombinase and combinatorial expression using promoters whose expression uniquely overlaps in the cell(s) of interest. Using this approach, it was shown that ASH photoactivation triggers withdrawal behaviours mimicking the endogenous response [50,59]. The strength of the optogenetic activation of the ASH neurons directly correlated with the magnitude of the behavioural response [50,60].…”
Section: Sensory Systemsmentioning
confidence: 99%
“…In addition, 5-HT (SER-1, MOD-1), OA (SER-6), and TA (TYRA-3) receptors also function downstream in the ASH circuit directly or outside the circuit to modulate aversive behavior, as described more fully below (Hapiak, unpublished;Harris et al 2009Harris et al , 2010Mills et al 2011). The ASHs are ''on'' neurons, i.e., calcium signaling increases after ligand addition, and, as noted above, ASH activation by a variety of different stimuli, including nose touch and soluble repellents, initiates significant increases in intracellular calcium in vivo (Ezcurra et al 2011;Hilliard et al 2005;Mills et al 2011). However, the monoaminergic modulation of ASH signaling appears to be both stimulus modality and intensity dependent.…”
Section: Monoamines Modulate Aversive Responses Mediated By the Ash Smentioning
confidence: 93%
“…For example, ASH-mediated aversive responses are enhanced by food or 5-HT and can be modulated by dopamine (DA) and inhibited by TA and OA. Receptors for 5-HT (SER-5), DA (DOP-3, DOP-4), and OA (OCTR-1, SER-3) appear to function directly in the ASHs to differentially modulate aversive behavior, although the role of these receptors in modulating ASH signaling is still only cursorily understood (Ezak and Ferkey 2010;Ezcurra et al 2011;Harris et al 2009;Mills et al 2011;Wragg et al 2007). In addition, 5-HT (SER-1, MOD-1), OA (SER-6), and TA (TYRA-3) receptors also function downstream in the ASH circuit directly or outside the circuit to modulate aversive behavior, as described more fully below (Hapiak, unpublished;Harris et al 2009Harris et al , 2010Mills et al 2011).…”
Section: Monoamines Modulate Aversive Responses Mediated By the Ash Smentioning
confidence: 98%